ChemInform Abstract: A C—H Functionalization Protocol for the Direct Synthesis of Benzobisthiazole Derivatives. Issue 7 (29th January 2015) - Bon, Jennifer L.; Feng, Daijun; Marder, Seth R.; Blakey, Simon B.
Abstract Moreover, this method is successfully applied in the syntheses of cruciform (VII) and thiazolothiazole (VIII).